Taṭwīru Ṭarzi Al-Masyrū‘i Al-Asāsiyyi At-Ta'allumiyyi bi Mabdai-l Ahliyyah At-Tiknūlūjiyyah li Taḥsīni Kafā`ati Kitābati-l Lugah Al-‘Arabiyyah Wa Ibdā'i-l Fikri - Rifda Haniefa; Eka Lutfiyatun (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2023)
Arabic writing skills in the modern era are not only done with conventional media such as paper and blackboards, but also are applied with the help of digital media as one of the pillars of digital literacy. Arabic language learning at SMP Nurussalam Depok is carried out in a language laboratory, but the use of laboratory computers is still limited only as a provider of material and has not been used for making projects that can optimize Arabic writing competence and hone students' creativity. Creative Thinking becomes urgent in modern times. Improving creative thinking and writing in Arabic can be done by implementing Project Based Learning (PjBL). The research problems are how to develop a digital literacy based PjBL model to optimize Arabic writing skills and creative thinking, its validity, and its effectiveness, while the aims are to find out the form of digital literacy based PjBL model development to optimize Arabic writing competence and creative thinking, as well as the results of its validity and effectiveness. Using the method of Research and Development (R&D), the data comes from tests, questionnaires, and observations. The research subjects were 20 students of class IX at SMP Nurussalam Depok. Product validation value is 88.33 (very feasible). The PjBL model based on digital literacy is effective in optimizing Arabic writing competence and creative thinking. The average pretest<posttest is 67.85<89.90 with a significance of 0.00<0.05. The average value of creative thinking is 82.22 or very suitable for the uniqueness of ideas, meaningful product creation, process suitability, and motivation. Hopefully educators can develop and utilize the models that have been developed for learning.